A rare presentation: A case report of osseous metaplasia and mature bone formation in a follicular adenoma of the thyroid. (2017) - Aurora, Nadia; Hashmi, Insia; Misra, Subhasis; Aydin, Nail
Highlights: Osseous metaplasia and bone formation may be seen in a broad spectrum of diseases involving the thyroid gland especially in malignant neoplasms of the thyroid gland. However, this differentiation is not unique to malignant neoplasms. It may also be encountered in follicular adenomas of the thyroid. Awareness of thyroid nodules undergoing hemorrhagic, cystic, and fibrotic changes, as well as calcification and ossification is paramount in proper diagnosis and treatment of these pathologies. Particularly, patient's history, associated risk factors and clinical presentation are the most important factors to consider in clinical differentiation of malignant and benign diagnoses. All ossifications in a thyroid nodule should be considered suspicious for malignancy until proven otherwise. Abstract: Introduction: Cases of multinodular goiter, thyroid hyperplasia, follicular adenoma, papillary thyroid carcinoma, and anaplastic thyroid carcinoma have been reported with histopathologic findings of osseous metaplasia (OM), bone marrow metaplasia (BMM), ectopic bone formation (EBF), ossification, and extramedullary hematopoiesis (EMH). To date no report of a follicular adenoma with OM and mature EBF in the absence of EMH has been reported in the English language. Presentation of case: 63-year-old woman with an incidental finding of thyroid nodule unable to be biopsied. One area was found to contain OM with mature EBF and without vascular invasion. The surrounding tissue was unremarkable, and no malignancy was found. Discussion: Ectopic bone formation and osseous metaplasia in a thyroid nodule has an extensive differential diagnosis, from thyroid related pathologies to parathyroid causes, congenital syndromes, and hamartomas. A common theory amongst these is the role of basic fibroblast growth factor (bFGF) and bone morphogenetic protein-2 (BMP-2), signaling factors involved in cellular proliferation and growth. Conclusion: This is the first case report of a follicular adenoma with OM and EBF in the absence of EMH. In this case, this adenoma was an incidental finding and the patient had no symptoms or accompanying laboratory abnormalities. Her benign presentation underscores the importance of awareness of the more common changes a thyroid nodule can undergo, such as hemorrhagic, cystic, and fibrotic changes, as well as the rarer changes of calcification with eventual ossification.